1982
DOI: 10.1046/j.1537-2995.1982.22282177122.x
|View full text |Cite
|
Sign up to set email alerts
|

A serum factor which inhibits serologic reactions with enzyme-treated red blood cells

Abstract: Two patients' sera inhibited agglutination of enzyme-treated red blood cells by antibodies. This blocking effect was detected by using a mixture of antibodies as an enzyme test reagent for the routine control of a two-stage papain test. The blocking factor appeared to be IgG and its effect was complement dependent. It blocked reactions with red blood cells treated with papain, bromelin, or ficin. Reactions with both IgM and IgG antibodies of various specificities were blocked. The presence of the blocking fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…1,8 Thus, each red cell attracts fewer ions from the suspending medium (usually saline) and reduces the zeta potential. 19 The minimum distance between red cells decreases, permitting them to move closer together. 6,8 This allows some antigens to become more accessible to their corresponding antibody, thereby allowing these cells to agglutinate in a saline medium.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 Thus, each red cell attracts fewer ions from the suspending medium (usually saline) and reduces the zeta potential. 19 The minimum distance between red cells decreases, permitting them to move closer together. 6,8 This allows some antigens to become more accessible to their corresponding antibody, thereby allowing these cells to agglutinate in a saline medium.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation revealed the pres ence of a papain inhibitor as described by Lown et al [4], Amniotic fluid AOD45o at 30 weeks gesta tion indicated a moderately affected baby. Fetal cells, obtained by fetal sampling at 32 weeks gestation, were group 0 Rh(D) pos itive , DAT positive (score 5).…”
mentioning
confidence: 66%